Pola Perkembangan Sintaksis Bahasa Inggris pada Anak - Liliek Soepriatmadji (Universitas Stikubank (UNISBANK) Semarang, 2015)
This study is aimed at: (1) construing the pattern at which the children’s English syntax develops; (2) explaining children’s mean length of utterance (MLU). The data were downloaded from YouTube.com. Categorical analysis was applied in order to achieve the objectives of this study. The findings indicate that (1) the pattern at which the children’s English syntax develops could be traced from three different phases: (a) linguistically unpatterned, as the language interaction does not exist yet. The children’s daily activities relate to opening mouth, closing mouth, yawning, blinking, moving head, and non-speech activities (crying, producing speech-like sounds: hee…, eeg…eeg), (b) simple linguistic pattern, as the language interactions are in the forms of babbling (ta ta ta), holophrase (doll) and two-word expression (Daddy go). They are also accompanied with non-speech activities (laughing, screaming, and producing speech-like sounds: heee, he he, eh eh, aahh, uuh, uum), and (c) linguistically patterned, as the language interaction is created in true speech – complete utterances with (a) subject-finite elements, (b) various sentence types, (c) various language functions and speech acts. (2) the MLUs of the true speech created by children are 3,57 (three years), 5,09 (four years), and 7,53 (five years). Keywords: syntax, MLU, linguistically unpatterned, simple linguistic pattern, linguistically patterned, babbling, holophrase, two-word expression, true speech